Pendampingan Psikologis Anak Usia Dini Karen Kurangnya Figur Orang Tua (Studi Kasus Ra Muslimat NU 127 Ngrogung) - Endang Diyahayu Maharani; Muhammad Misbahuddin (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The lack of parental figures in early childhood is one of the factors that can influence children’s psychological development. Young children need emotional attachment, guidance, and role models from parents in shaping their character, sense of security, and self-confidence. This study aims to examine the impact of the absence of parental figures on the psychological condition of early childhood at RA Muslimat NU 127 Ngrogung. The research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The results reveal that the lack of parental roles leads to anxiety, low learning motivation, difficulties in social interaction, and limited independence among children. However, the school strives to minimize these impacts through love-based learning approaches and intensive mentoring.